2013
DOI: 10.1021/ie4026852
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Effective Gold Leaching from a Desulfurized Gold Ore Using Acidic Sodium Chlorate Solution at Low Temperature

Abstract: The effects of various leaching conditions for gold extraction from sulfur-containing gold ore using acidic sodium chlorate solution were investigated. The contents of gold and sulfur from the ore were 55.7 g/ton and 11.67 wt %, respectively. It was found that the presence of sulfur greatly inhibited gold extraction. The optimal desulfurization temperature, desulfurization time, leaching temperature, leaching time, adding rate of NaClO 3 , HCl concentration, weight ratio of NaCl to sample, agitation speed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…On the basis of the available observations, one can conclude that CAP exhibits the capability toward complexation-promoted oxidative dissolution of elemental Au to Au­(I). Gold is the noble metal, and aside from the several strong oxidizers such as aqua regia, hot H 2 SeO 4 , halogens, Me 3 PI 2 , hypochlorite (ClO – ) and chlorate (ClO 3 – ), there are very few classes of compounds capable of promoting oxidative dissolution of Au(0) under the mild conditions. The mechanisms underlying those reactions always imply complexation of Au with the ligands having strong affinity for gold, thereby shifting the redox potential of Au(0)/Au­(I,III) pair toward negative values with the formation of Au­(I) or Au­(III) species.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the available observations, one can conclude that CAP exhibits the capability toward complexation-promoted oxidative dissolution of elemental Au to Au­(I). Gold is the noble metal, and aside from the several strong oxidizers such as aqua regia, hot H 2 SeO 4 , halogens, Me 3 PI 2 , hypochlorite (ClO – ) and chlorate (ClO 3 – ), there are very few classes of compounds capable of promoting oxidative dissolution of Au(0) under the mild conditions. The mechanisms underlying those reactions always imply complexation of Au with the ligands having strong affinity for gold, thereby shifting the redox potential of Au(0)/Au­(I,III) pair toward negative values with the formation of Au­(I) or Au­(III) species.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the result, the reagent cost to treat 1 t of anode slime was 16.8 $/t; as a comparison, the reagent cost of gold extraction using a hydrometallurgy process was usually higher. The reagent cost for thiosulfate leaching, thiourea leaching, and chlorate leaching to process 1 t of anode slime was 331 $/t, 1120 $/t, and 146 $/t, respectively (Table ). The result demonstrated that our method was highly competitive in reagent cost.…”
Section: Resultsmentioning
confidence: 99%
“…Gold conversion was about 70.38% at 15 min and then slightly increased to 92.9% as the reaction time extended from 15 to 60 min. For the hydrometallurgical process, it usually took hours or even dozens of hours to achieve optimal gold yield. The outstanding reaction efficiency of the approach was likely to ensure low energy consumption.…”
Section: Resultsmentioning
confidence: 99%
“…1 An acidic goldcontaining chloride filtrate collected from the leaching experiments was thus obtained. The concentrations of gold and hydrochloric acid from the leachate were 3.43 ppm and ∼3.33 M, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of gold and hydrochloric acid from the leachate were 3.43 ppm and ∼3.33 M, respectively. The gold ions existed mainly in the form of chloroauric ([AuCl 4 – ]) ions . The reduction of Au­(III) to nanoparticles of metallic Au has been reported using reducing agents such as ascorbic acid, Sn­(II), glycerol, hydrogen peroxide, glucose, trisodium citrate, and dimethylamine borane .…”
Section: Introductionmentioning
confidence: 99%